Directly engaging with People with lived experiences of mental illness from the communities in India - Amanpreet Kaur, Ph.D., M.Phil; Sudha Kallakuri, M.Sc; Mercian Daniel, Ph.D; Sandhya K. Yatirajula, Ph.D; Siddhardha Devarapalli, Ph.D; Pallab K. Maulik, M.D., Ph.D (Elsevier, 2021)
Stigma and discrimination dissuade people with mental illnesses from talking openly about their problems. In India, these experiences are influenced by local cultural factors. Interventions to reduce mental health stigma in India indicated that very few studies have involved people with lived experiences (PWLEs) of mental illness and their families. As evidence shows that having interpersonal contact with a person with mental illness reduces stigma, we present our personal experiences in engaging with PWLEs of mental illness directly from the community. We discuss here the challenges experienced while engaging with PWLEs of mental illnesses because of stigma and feared discrimination from others in the community. Lessons learnt as part of past and ongoing mental health projects have been highlighted. Our experiences underline importance of involving local psychiatric facilities, community health workers and engagement with communities from the very outset as some key steps in increasing the chances of engaging with such individuals. Future strategies could make use of plethora of multi-media approaches such as, videos, films, drama, animations, podcasts, and audio-recordings aiming to reduce stigma and improve mental health literacy as part of anti-stigma interventions.